Heat and mass transfer for MHD nanofluid flow on a porous stretching sheet with prescribed boundary conditions - Sadighi, Sina; Afshar, Hossein; Jabbari, Mohsen; Ahmadi Danesh Ashtiani, Hossein (Case studies in thermal engineering, 2023)
A theoretical study is conducted in order to scrutinize the thermodynamic first law of the MHD nanofluid flow with an inclined magnetic field, radiation, heat source/sink, viscous dissipation, Joule heating, concentration power-law exponent, and the chemical reaction on a porous stretching surface immersed within a permeable Darcian medium. Cobalt ferrite nanoparticles (CoFe2O4) have been combined with pure water to form a nanofluid called CoFe2O4/H2O. The controlling mathematical equations for MHD nanofluid flow are transformed through similarity transformation into non-dimensional equations. The exact solutions for the energy and mass transfer equations are provided in terms of confluent hypergeometric function. The effects of controlling parameters on the velocity, temperature, and concentration profiles are discussed and illustrated with figures and tables. According to the results, increasing the concentration power-law exponent yields a rise in the Sherwood number (PSC) magnitude and the wall concentration (PMF). Furthermore, the 3-D plots showed that the skin friction coefficient is directly related to the Hartmann number, suction parameter, and nanoparticle volume fraction parameter.